Culture, institutions, and economic development : a study of eight European regions - Keating, Michael, 1956-; Deschouwer, Kris.; Loughlin, John. (Cheltenham ; Northampton, MA : Edward Elgar Pub., 2003)
"This book reviews the debate surrounding the construction of regions and presents eight case studies to illustrate how they are shaped and reshaped in a variety of different ways. The authors find that while the regions exhibit some common patterns, there are significant variations, indicating that there is no definitive model of regional development." "This book offers a systematic comparison of eight distinct regions and stateless nations, each with its own historical identity, but which is constantly being rebuilt in changing economic and political conditions. Avoiding economic or cultural determinism, the authors show how region-builders can shape their own responses to global challenges to produce models of development reflecting differing understandings and social compromises." "Culture, Institutions and Economic Development will be welcomed by academics within the fields of regional studies, European studies and political science."--BOOK JACKET.
1. Culture, Institutions and Development -- 2. The New Regionalism -- 3. Spain: Catalonia and Galicia -- 4. Belgium: Flanders and Wallonia -- 5. France: Brittany and Languedoc -- 6. The United Kingdom: Scotland and Wales -- 7. Conclusion.
Includes bibliographical references and index.
Keywords: Regional economic disparities; Europe -- Economic conditions -- 1945- -- Case studies; Europe -- Social conditions -- Case studies; Europe -- Civilization -- 1945-